ISLAMIC EDUCATION AND THE CHALLENGES OF COVID 19 IN MICHAELOTEDOLA COLLEGE OF PRIMARY EDUCATION, NOFORIJA-EPE, LAGOS STATE. - Agbabiaka- Mustapha, Muinat A. (Religions' educator, 2020)
hereare152CollegesofEducationinNigeria,consistingof21Federal,82Privateand49stateCollegesofEducation.MichaelOtedolaCollegeofPrimaryEducationwasestablishedinDecember,1994duringtheadministrationofSirMichaelAgboladeOtedolaasLagosStateGovernor.Oneofthemainobjectivesofestablishingthecollegewastoprovidewellqualified(non-graduates)primaryschoolteachersinaccordancewiththerequirementsofbothfederalandstatesministriesofeducation.TheCollegehasbeenachievingthisobjectivefrominceptiontilldatebytrainingandcertifyingteachersinvariousfieldsofstudiesincludingIslamicStudieswhichisthefocusofthispaper.Inrecognitionofthefactthatreligionplaysasignificantroleinhistoryandsociety,studyofreligionisessentialtounderstandingboththenationandtheworldandthedevelopmentofandpurificationofthehumansoul.ThisstudyexaminesthechallengesofCOVID19ontheteachingandlearningofIslamicStudiesinMOCPEDandproposedthatsuitablelearningmaterialsinagoodlearningenvironmentshouldbeprovidedbythegovernmentandthecollegeauthoritytoenhanceeffectiveteachingandlearningofIslamicStudiesamidstandbeyondCOVID19pandemic.Usingdescriptivemethod/qualitativeresearchapproach,focusgroupdiscussionwasusedtocollectdata.Hence,thestudyaroseoutofthefearandconcernfortheteachingandlearningofIslamicStudiesifthereisanotherlockdownnecessitated by the second phase of COVID 19.